Good Governance in Jordan: Reality and Future Prospects - AL-Refai, Mohammed (The Arab Journal of Administration, 2019)
The present study aims to investigate the current situation of good governance in the Hashemite Kingdom of Jordan. The study depends mainly on the Worldwide Governance Indicators (WGI) that have been issued in 1996 by the World Bank (WB) and comprise from six sub indicators; Control of Corruption, Government Effectiveness, Political Stability and Absence of Violence, Regulatory Quality, Rule of law, and Voice and Accountability. The study carried out during the period (1996- 2014). The study revealed that the Hashemite Kingdom of Jordan ranking in the indicators of the rule of law, Government Effectiveness, Control of Corruption, and Regulatory Quality has been above the average and ranged between (69.7% -53.2%), while the Hashemite Kingdom of Jordan ranking in the indicators of Political Stability and Absence of Violence, Voice and Accountability, below the average and ranged between (23.2%- 46.2 %). The results of the study also showed that the Hashemite Kingdom of Jordan is progressed in a positive way during the study period with indicators of the Control of Corruption, Regulatory Quality and the rule of law, while a negative decline in the indicators of Government Effectiveness, Political Stability and Absence of Violence, Voice and Accountability. The study provides a number of recommendations the most important of them include the setting a system of accountability and monitoring for the performance of government officials in the case of abuse of public office, achieving personal interests or failure in managing institutions and waste of money; besides setting of a clear strategy which is applicable for implementation to reduce the administrative flabbiness and to eliminate the bureaucracy in the public sector; there is a need to give the government a period of time required for the implementation of programs that are important for the stability of public policy and finally formulating a new law for elections process that govern the representative councils that meets the aspirations of the citizens and to strengthen the democratic process and to ensure broad participation in the elections process.